Identification and Biological Activity of Synthetic Macrophage Inducible C-Type Lectin Ligands - Braganza, Chriselle D.; Teunissen, Thomas; Timmer, Mattie S. M.; Stocker, Bridget L. (Frontiers in Immunology, 2018)
The Macrophage Inducible C-Type Lectin (Mincle) is a pattern recognition receptor able to recognise both damage-associated and pathogen-associated molecular patterns, and in this respect, there has been much interest in determining the scope of ligands that bind Mincle and how structural modifications to these ligands influence ensuing immune responses. In this review we will present Mincle ligands of known chemical structure, with a focus on ligands that have been synthetically prepared, such as trehalose glycolipids, glycerol-based ligands, and 6-acylated glucose and mannose derivatives. The ability of the different classes of ligands to influence the innate, and consequently, the adaptive, immune response will be described, and where appropriate, structure-activity relationships within each class of Mincle ligands will be presented.